Une collaboration entre différents acteurs du patrimoine et de la recherche : la numérisation et l’indexation des chartes et autres documents de la Trinité de Fécamp conservés au Palais Bénédictine - Pierre Bauduin; Michaël Bloche; Thierry Buquet; Sébastien Roncin (Tabularia)
The paper presents a collaboration between the company Bacardi Limited France, the Archives départementales de la Seine-Maritime and Craham, for the digitization and scientific valorisation of the ancient collections of the abbey of Trinity of Fécamp, kept in the Palais Bénédictine at Fécamp. First, the paper exposes the scientific context of the project genesis and the cooperation through an agreement between the three institutions; secondly the article presents the collection of the Fécamp documents which are concerned by the operation, among them are found some of the oldest Norman charters and other recently rediscovered documents (2012). A part of these items have been included in a vast digitization programme of the charters prior to 1204 kept at the Archives départementales of Seine-Maritime, and into a research enquiry on the muniments of the abbey of Fécamp before 1190, which has lead to a PHD dissertation, finished in 2019 as well. I was thus possible, thanks to digital resources, to offer a virtual reconstruction of these muniments. Other outcomes have been made possible, through the Vexicaen project and the recent evolution of the Scripta database (Norman charters before 1300): in particular, the integration of digital pictures in this database.